2016
DOI: 10.1016/j.jadohealth.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The Detroit Young Adult Asthma Project: Pilot of a Technology-Based Medication Adherence Intervention for African-American Emerging Adults

Abstract: Purpose To conduct a randomized controlled pilot of a multi-component, technology-based intervention promoting adherence to controller medication in African American emerging adults with asthma. The intervention consisted of two computer-delivered sessions based in Motivational Interviewing (MI) combined with text messaged reminders between sessions. Methods Participants (N=48) were 18–29 years old, African American, with persistent asthma requiring controller medication. Participants had to report poor medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 37 publications
1
46
0
Order By: Relevance
“…A repeated measures design (baseline and 1-, 3-, 6-, 9-, and 12-months postbaseline) will be used with the primary outcome being adherence to daily controller medications and the secondary outcome as asthma control. We expand on the pilot study [ 55 ] by testing the long-term effects over 1 year, which allows us to account for seasonal variability of symptoms in a young, urban population [ 58 , 59 ], to gain understanding of the long-term impact on adherence behavior, and to allow trajectory analyses of adherence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A repeated measures design (baseline and 1-, 3-, 6-, 9-, and 12-months postbaseline) will be used with the primary outcome being adherence to daily controller medications and the secondary outcome as asthma control. We expand on the pilot study [ 55 ] by testing the long-term effects over 1 year, which allows us to account for seasonal variability of symptoms in a young, urban population [ 58 , 59 ], to gain understanding of the long-term impact on adherence behavior, and to allow trajectory analyses of adherence.…”
Section: Methodsmentioning
confidence: 99%
“…The MCTI was tested in a pilot randomized controlled trial [ 54 , 60 ] and is an integration of several technology-based components. The intervention group will receive 2 sessions of computer-delivered MI via CIAS software (Interva, Detroit, MI) programmed to target adherence to medications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the control arm, 29.9% of patients missed at least 20% of doses, while 27.3% and 17.0% and 13.9% missed the same amount of doses in the text reminder, smart packaging, and combined arms, respectively . However, other clinical studies and meta‐analyses have indicated that text message reminders and related digital health apps can increase medication adherence …”
Section: Medication Adherencementioning
confidence: 99%
“…This realization has led to the development of SMS text message-based pilot and feasibility studies targeting various behaviors such as the medication adherence, HIV prevention, healthy eating, and physical activity [ 21 - 25 ]. Although these studies demonstrate the acceptability, feasibility, and potential effectiveness of SMS text message interventions designed for African American adults, few have utilized randomized controlled designs [ 22 ], and fewer were specifically designed to promote weight loss [ 26 ]. Therefore, the purpose of the Lifestyle Changes Through Exercise and Nutrition (LEAN) study was to test the feasibility (SMS text message tolerance and satisfaction) and effectiveness (compared with a control group) of utilizing SMS text messages to promote weight loss in African American adults enrolled in a church-based weight loss program.…”
Section: Introductionmentioning
confidence: 99%